Efektivitas Dental Health Education Menggunakan Media Audio Visual dalam Meningkatkan Pengetahuan Siswa Sekolah Dasar - Pitoy, Anastasia D.; Wowor, Vonny N. S.; Leman, Michael A. (e-GiGi, 2021)
Abstract: Basic Health Research of the Ministry of Health of the Republic of Indonesia showed that 93% of Indonesian children experience dental caries. Dental health education (DHE) is the provision of information in the form of a comprehensive understanding of dental and oral health and the determinants that affect individuals and communities. Giving DHE to children must be done in an appropriate and effective way. This study was aimed to to determine the effectiveness of DHE using audio-visual media to elementary school students. This was a literature review study using the PubMed, Google Scholar, Science Direct, and Clinical Key databases. Then the literatures were selected according to the inclusion and exclusion criteria and a critical appraisal was carried out to obtain relevant and worthy literatures. After going through the study selection, nine literatures were accepted. All literatures showed an increase in students' knowledge about dental and oral health after the DHE using audio-visual media. In conclusion, elementary school students' knowledge about dental and oral health increased significantly after DHE using audio-visual media.Keywords: dental health education (DHE); audio visual media; elementary schoolâ€™s studentsÂ Abstrak: Hasil Riskesdas Kementrian Kesehatan Republik Indonesia menunjukkan 93% anak Indonesia mengalami karies gigi. Dental health education (DHE) adalah pemberian informasi berupa pemahaman yang komprehensif tentang kesehatan gigi dan mulut serta faktor penentu yang memengaruhi individu dan komunitas. Pemberian DHE pada anak harus dilakukan dengan cara yang tepat dan efektif. Penelitian ini bertujuan untuk mengetahui efektivitas dental health education menggunakan media audio visual pada siswa sekolah dasar. Jenis penelitian ialah suatu literature review mengguanakan database PubMed, Google Scholar, Science Direct, dan Clinical Key. Literatur yang diperoleh kemudian diseleksi sesuai dengan kriteria inklusi dan eksklusi serta dilakukan critical appraisal untuk mendapat literatur yang relevan dan layak diteliti. Setelah melalui seleksi studi, didapatkan sembilan literatur untuk diulas. Semua literatur menunjukkan terjadi peningkatan pengetahuan siswa tentang kesehatan gigi dan mulut setelah DHE menggunakan media audio visual. Simpulan penelitian ini ialah pengetahuan siswa sekolah dasar tentang kesehatan gigi dan mulut meningkat secara bermakna setelah pemberian DHE menggunakan media audio visual.Kata kunci: dental health education (DHE); media audio visual; siswa sekolah dasar